2022
DOI: 10.5599/jese.1360
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of folic acid using a modified screen printed electrode

Abstract: In this work, an electrochemical sensor was established for the detection of folic acid based on Ni-BTC (BTC = benzene-1,3,5-tricarboxylic acid) metal-organic framework (MOF) modified screen-printed electrode (SPE). Electrochemical techniques (cyclic voltammetry (CV), differential pulse voltammetry (DPV), linear sweep voltammetry (LSV) and chrono­ampere­metry (CHA) were used for the detection of folic acid at Ni-BTC MOF modified SPE. The results indicate that the as-prepared sensor has a good electrocatalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In addition, the conventional addition method was used to assess the viability of the Ni-BTC MOF/SPE sensor's ability to detect B9 in real samples. 74 Abid et al suggested a 2-D MoS 2 nanosheet with applied gold nanoparticles at the SPCE (AuNPs-MoS 2 /SPCE)-based electrochemical sensor for detecting vitamin B9. The AuNPs-MoS 2 / SPCE sensor showed a good sensitivity of 20.636 mA mM −1 cm −2 , in the linear concentration range of 0-20 mM with an LOD of 1.04 mM.…”
Section: Various Transducing Matrixes For Vitamins Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the conventional addition method was used to assess the viability of the Ni-BTC MOF/SPE sensor's ability to detect B9 in real samples. 74 Abid et al suggested a 2-D MoS 2 nanosheet with applied gold nanoparticles at the SPCE (AuNPs-MoS 2 /SPCE)-based electrochemical sensor for detecting vitamin B9. The AuNPs-MoS 2 / SPCE sensor showed a good sensitivity of 20.636 mA mM −1 cm −2 , in the linear concentration range of 0-20 mM with an LOD of 1.04 mM.…”
Section: Various Transducing Matrixes For Vitamins Sensingmentioning
confidence: 99%
“…In addition, the conventional addition method was used to assess the viability of the Ni–BTC MOF/SPE sensor's ability to detect B9 in real samples. 74 …”
Section: Introductionmentioning
confidence: 99%
“…The chemical modification of inert substrate electrodes offers significant advantages in the design and development of electrochemical sensors. The properties of chemically modified electrodes that have driven their development include increased selectivity and sensitivity, chemical and electrochemical stability, larger usable potential windows, and resistance to fouling [23][24][25][26][27][28][29][30][31][32][33][34][35]. The incorporation of nanomaterials has had a great impact on the development of electrochemical sensors [36][37][38][39][40].…”
Section: A D V N C E D O N L I N E a R T I C L Ementioning
confidence: 99%
“…The chemical modification of inert substrate electrodes offers significant advantages in the design and development of electrochemical sensors [48][49][50][51][52]. In operations, the redox-active sites often shuttle electrons between a solution of the analyte and the substrate electrodes, with a significant reduction of the activation overpotential [53][54][55]. A further advantage of chemically modified electrodes is that they are less prone to surface fouling and oxide formation compared to inert substrate electrodes [56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%